Analysis of Cultural Literacy Learning Based on Local Wisdom to Strengthen the Profile of Pancasila Students - Andita, Septya Bayu; Tirtoni, Feri (Universitas Pendidikan Mandalika, 2024)
This study aims to analyze local wisdom-based cultural literacy learning to strengthen the profile of Pancasila students in the dimension of Global Diversity integrated into Pancasila Education subjects. The research method employed a descriptive method with a qualitative approach. The subjects of this study were fourth-grade students and teachers of SDN Gelam 1 Candi in the 2023/2024 school year, totalling 24 students. Data collection techniques were carried out through observation, interviews, and documentation. This data analysis technique used interactive model analysis consisting of data reduction, data presentation, and conclusion drawing. In testing the validity of the data obtained by using the triangulation techniques. The results of this study indicated that local wisdom-based cultural literacy learning can strengthen the profile of Pancasila students in the Global Diversity dimension integrated into Pancasila Education subjects through various learning activities, such as making Pop Up Book of Sidoarjo Local Wisdom and LKPD integrated with local wisdom of Sidoarjo City. In addition, it can also improve the cultural literacy skills of students who can respond to local cultural diversity and cultural issues to face cultural shifts in the future. Students can also show a sense of pride and participate in preserving the local culture of Sidoarjo by making Udeng Pacul Gowang an icon of Sidoarjo City.